Intermediate catheter use is associated with intraprocedural rupture during coil embolization of ruptured intracranial aneurysms: a retrospective propensity score-matched study - Fuga, Michiyasu; Ishibashi, Toshihiro; Aoki, Ken; Kato, Naoki; Kan, Issei; Hataoka, Shunsuke; Nagayama, Gota; Sano, Tohru; Tanaka, Toshihide; Murayama, Yuichi (Frontiers in Neurology, 2024)
Introduction: An intermediate catheter (IMC) may pose a risk of intraprocedural rupture (IPR) during coil embolization of ruptured intracranial aneurysms (RIAs), because the pressure on the microcatheter and coil might be more direct. To verify this hypothesis, this study explored whether use of an IMC might correlate with an increased rate of IPR during coil embolization for RIAs. Methods: We retrospectively reviewed 195 consecutive aneurysms in 192 patients who underwent initial coil embolization for saccular RIAs at our institution between January 2007 and December 2023. Patients were divided into two groups with aneurysms treated either with an IMC (IMC group) or without an IMC (non-IMC group). To investigate whether IMC use increased the rate of IPR, a propensity score-matched analysis was employed to control for age, sex, maximal aneurysm size, neck size, bleb formation, aneurysm location, proximal vessel tortuosity, balloon-assisted coiling, type of microcatheter, and type of framing coil. Results: Ultimately, 43 (22%) coil embolization used IMC. In univariate analysis, the incidence of IPR was significantly higher in the IMC group compared with the non-IMC group (14.0% vs 3.3%, p=0.016). Propensity score matching was successful for pairs of 26 aneurysms in the IMC group and 52 aneurysms in the non-IMC group. The incidence of IPR was still significantly higher in the IMC group than in the non-IMC group (23.1% vs 3.8%, p=0.015). No significant differences in the incidences of ischemic complications and IMC-related parent artery dissection were observed between the two groups. Discussion: When using IMC for coil embolization of RIAs, the surgeons should be more careful and delicate in manipulating the microcatheter and inserting the coils to avoid IPR.